Pathogenesis of ovarian seromucinous borderline tumors - Mekan R. Orazov; Marina V. Kiseleva; Vladlena M. Pernay (LLC "MEDIAFORMAT", 2024)
he 2014 World Health Organization classification identifies ovarian seromucinous tumors as one of the six categories of epithelial ovarian tumors. Ovarian seromucinous tumors encompass adenomas, atypical proliferating (borderline) tumors, and invasive carcinomas. These tumors are exceedingly rare, with benign instances accounting for a mere 1% and 25% of borderline cases among all atypical proliferating tumors. The rarity of seromucinous cancer means its prevalence has not been thoroughly investigated, which has resulted in this group of tumors remaining incompletely researched.